2019
DOI: 10.1007/s10750-019-04043-w
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of the antibiotic resistance gene blaCTX-M in temperate Lake Maggiore

Abstract: The beta lactamase gene blaCTX-M, responsible of the resistance to cephalosporins, has been detected in microbes from hospitals to open waters. We studied the seasonality and stability of blaCTX-M in Lake Maggiore over 3 years and the role of potential inputs of allochthonous bacteria and/or antibiotic pollution in promoting its occurrence. blaCTX-M was mainly present from January to July in the pelagic microbial community and the gene occurrence was significantly related to low water temperature. To evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Contrary to what was expected, the bla CTX-M gene was found in low concentrations in the Katalinića WWTP effluent and in <LOQ or null concentrations in the other WWTPs. It has been hypothesized that urban WWTPs are the principal source of bla CTX-M for aquatic environments [23,51] because bla CTX-M harboring strains isolated in rivers and wastewater were found to be related to nosocomial strains of the same geographical area [79,80].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to what was expected, the bla CTX-M gene was found in low concentrations in the Katalinića WWTP effluent and in <LOQ or null concentrations in the other WWTPs. It has been hypothesized that urban WWTPs are the principal source of bla CTX-M for aquatic environments [23,51] because bla CTX-M harboring strains isolated in rivers and wastewater were found to be related to nosocomial strains of the same geographical area [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that people's probability of contracting gastrointestinal and non-gastrointestinal illnesses increases in correlation with aquatic recreational activities because of antibiotic-resistant bacteria and other community-acquired microorganisms [19,20]. Furthermore, frequent bathing in coastal waters has been shown to be associated with gut colonization by E. coli harboring ARGs, including, for example, bla CTX-M genes, which provide resistance to clinically relevant antibiotics (cefotaxime) and which are easily mobilized via horizontal gene transfer (HGT), thus increasingly found in natural environments as well as in WWTPs [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of the ARGs measured in Lake Maggiore are available from 2013 (detected monthly) and are characterized by large differences among genes (Di Cesare et al 2015 , Eckert et al 2019a , CIPAIS 2021 ): bacteria carrying sul 2 and tet A are constantly present and abundant in the waters of the lake in the last 10 years, bla CTX-M in 2015–6 was only sporadically quantifiable, missing the seasonality characterizing other years (present in winter/spring, absent for the rest of the year; Eckert et al 2019 ). The sul 2 gene, widely distributed and abundant in the microbiome of the lake, was also discharged in large numbers from the rivers (mainly from Toce, Tresa and Bardello), but without any correlation between loads and abundances in the lake.…”
Section: Discussionmentioning
confidence: 99%
“…This area hosts about 640000 inhabitants (CIPAIS 2003 ) and a large number of seasonal tourists, mainly in spring and summer (the number of tourists hosted in the watershed of the Lake in 2015–6 was between 4 and 5 million; USTAT Canton Ticino 2017 , ISTAT 2017a ). From 2013, the horizontal and vertical distribution of ARGs in Lake Maggiore has been assessed monthly by monitoring programs funded by the International Commission for the Protection of Italian-Swiss Waters (Di Cesare et al 2015 , CIPAIS 2018 , Eckert et al 2019a , Di Cesare et al 2020 , CIPAIS 2021 ). However, the relative contribution of the ARGs released from its watershed through the tributary rivers or from the WWTP effluents directly discharged into the lake to the resistome of the lake has never been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation